Role performance of school supervisors in the division of Quezon City and Rizal province and its implications for supervision in Thailand - Chantaramai, Sobhon 1936- ([Quezon City s.n.], 1973)
The roles performed by 45 division and district supervisors of Quezon City and 60 of Rizal may be categorized into six areas ranked in the order of decreasing average mean value as follows: (1) instructional goals and objectives; (2) other activities not directly related to supervision; (3) improving teaching-learning process; (4) improving staff morale; (5) improving the curriculum and teaching materials and (6) research. These are often performed to a marked degree except roles of initiating curriculum improvement and development, working for increased salaries and more fringe benefits of teachers, and providing funds to support research of teachers. Secondary supervisors performed more and better than elementary supervisors. District supervisors often engaged in slightly more supervisory activities than secondary school supervisors.
Thesis (M. Ed.)--University of the Philippines.
Keywords: School superintendents and principals -- Quezon City; School management and organization -- Thailand; School superintendents and principals -- Rizal (Province).